2020
DOI: 10.1111/1365-2435.13722
|View full text |Cite
|
Sign up to set email alerts
|

Tree phylogenetic diversity structures multitrophic communities

Abstract: Plant diversity begets diversity at other trophic levels. While species richness is the most commonly used measure for plant diversity, the number of evolutionary lineages (i.e. phylogenetic diversity) could theoretically have a stronger influence on the community structure of co‐occurring organisms. However, this prediction has only rarely been tested in complex real‐world ecosystems. Using a comprehensive multitrophic dataset of arthropods and fungi from a species‐rich subtropical forest, we tested whether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 97 publications
(159 reference statements)
1
34
1
1
Order By: Relevance
“…Indeed, the identification of niche differences should be even more feasible throughout the phylogenetic than the functional approach 14 , 24 , because the latter would require the analysis of several traits most of which might be hard or impossible to measure 16 , 25 . Thus, phylogenetic diversity could represent more reliably niche differences than functional diversity 26 30 , but see Ref. 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the identification of niche differences should be even more feasible throughout the phylogenetic than the functional approach 14 , 24 , because the latter would require the analysis of several traits most of which might be hard or impossible to measure 16 , 25 . Thus, phylogenetic diversity could represent more reliably niche differences than functional diversity 26 30 , but see Ref. 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…Traps were emptied fortnightly (in total ten collections per trap) and catches were preserved in 70% ethanol until identification ( Schuldt et al 2011 ). Flight interception traps were installed close to the pitfall traps in 2010 ( Schuldt et al 2015a ; Staab et al 2021 ). Ground beetles were sorted and body length was measured for biomass calculation (see section Statistical analysis ).…”
Section: Methodsmentioning
confidence: 99%
“…Relationships between biodiversity and ecosystem functions and the effects of environmental variables have been studied extensively in this area (e.g., Schuldt et al 2010 ; Lang et al 2012 ; Staab et al 2014 ; Eichenberg et al 2015 ; Zou et al 2015 ; O’Brien et al 2016 ; Brezzi et al 2017 ). However, while the main abiotic and biotic drivers potentially shaping herbivore, decomposer and predator diversities have been studied (e.g., Schuldt et al 2011 ; Staab et al 2014 ; Schuldt et al 2015a ; Binkenstein et al 2018 ; Staab et al 2021 ) studies on ground beetles are still lacking for this National Park.…”
Section: Introductionmentioning
confidence: 99%
“…For insects, studies have suggested high correlations between phylogenetic structure and species cooccurrences across different areas (e.g. Ceccarelli et al 2020, Seifert et al 2020, Staab et al 2020). However, it is still unclear how phylogenetic distance and functional traits affect co-occurrence within two trophic levels (Gotelli & McCabe 2002, Kraft et al 2015.…”
Section: Introductionmentioning
confidence: 99%